2017
DOI: 10.1615/intjmedmushrooms.v19.i5.60
|View full text |Cite
|
Sign up to set email alerts
|

Colony Characteristics, Nucleoside Analog Profiles, and Genetic Variations of Medicinal Fungus Polycephalomyces nipponicus (Ascomycetes) Isolates from Northeast Thailand

Abstract: The entomopathogenic fungus Polycephalomyces nipponicus is known to have activity against human pathogenic bacteria and the malaria pathogen; however, information about its genetic variation is limited. In this study, cicada nymphs infected with entomopathogenic fungi were collected from various locations in the northeast of Thailand. Internal transcribed spacer sequencing was used to identify the fungal pathogen P. nipponicus. A total of 36 isolates of P. nipponicus from 6 provinces were investigated for vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0
1

Year Published

2019
2019
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 0 publications
1
1
0
1
Order By: Relevance
“…Among the fungal isolates, the Cod-KK1643 isolate had the most potent antifungal activity, as evidenced by large inhibition zones, relative to the antibiotic amphotericin B, and it had the lowest of MIC value. This result is in agreement with the finding that antifungal activity depends on the fungal strains [20]. Therefore, Cod-KK1643 was chosen for further studies on elucidation of antifungal activity with time kill assay and SEM.…”
Section: Discussionsupporting
confidence: 88%
“…Among the fungal isolates, the Cod-KK1643 isolate had the most potent antifungal activity, as evidenced by large inhibition zones, relative to the antibiotic amphotericin B, and it had the lowest of MIC value. This result is in agreement with the finding that antifungal activity depends on the fungal strains [20]. Therefore, Cod-KK1643 was chosen for further studies on elucidation of antifungal activity with time kill assay and SEM.…”
Section: Discussionsupporting
confidence: 88%
“…Nhưng sự biến đổi đặc điểm hình thái chỉ có thể quan sát ở một số trường hợp (A. Sangdee, Sangdee, Seephonkai, Jaihan, & Kanyaphum, 2017). Kết quả nghiên cứu phát sinh loài phân tử của Sung, Sung, Jones, và Spatafora (2007) Mặt khác, nhiều loài nấm kí sinh trên ấu trùng ve sầu có sự nhầm lẫn về hình dạng dẫn đến việc đặt tên không đúng khi quan sát hình thái đại thể của chúng (Jaihan & ctg., 2021).…”
Section: Giới Thiệuunclassified
“…exhibit significant potential for producing a diverse range of secondary metabolites. For instance, Pleurocordyceps nipponicus and P. phaothaiensis contain natural antioxidant, antibacterial, antitumorigenic, anti-inflammatory, and antimicrobial compounds (Sangdee et al, 2017 ; Somsila et al, 2018 ; Sonyot et al, 2020 ). Gokhale et al ( 2020 ) reported that the secondary metabolites of P. sinensis have antibacterial potential.…”
Section: Introductionmentioning
confidence: 99%